2022
DOI: 10.1111/bjet.13281
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of student knowledge in game‐based learning with distributed representations of assessment questions

Abstract: Game-based learning environments hold significant promise for facilitating learning experiences that are both effective and engaging. To support individualised learning and support proactive scaffolding when students are struggling, game-based learning environments should be able to accurately predict student knowledge at early points in students' gameplay. Student knowledge is traditionally assessed prior to and after each student interacts with the learning environment with conventional methods, such as mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For instance, Bulut et al (2022) found that data gathered in online formative assessment activities, for example, scores and time features, can predict student performance in midterm and final exams. Emerson et al (2022) combined student log data collected in a game-based learning environment and the content from the post-test assessment questions, and developed an early prediction model of student achievements on a post-test. The authors showed that this approach can improve the performance and generalisability of prediction models, including the models that predict achievements of new students.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Bulut et al (2022) found that data gathered in online formative assessment activities, for example, scores and time features, can predict student performance in midterm and final exams. Emerson et al (2022) combined student log data collected in a game-based learning environment and the content from the post-test assessment questions, and developed an early prediction model of student achievements on a post-test. The authors showed that this approach can improve the performance and generalisability of prediction models, including the models that predict achievements of new students.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%
“…In the first group of studies, the authors harnessed learning analytics to support the assessment of course content comprehension. Bulut et al (2022) and Emerson et al (2022) demonstrated that combining learner trace‐data and data from formative assessments can be a viable approach to predicting learning performance of university students. For instance, Bulut et al (2022) found that data gathered in online formative assessment activities, for example, scores and time features, can predict student performance in midterm and final exams.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%
“…Malinova and Rahneva (Malinova & Rahneva, 2017) and Botelho et al (Botelho et al, 2023) proposed methods for automated question generation in English and mathematics respectively. Emerson et al (Emerson et al, 2022) introduced the use of fine-grained content for student performance prediction during tests. Transformer-based models for reading comprehension test generation were studied by Bulut and Yildirim-Erbasli (Bulut & Yildirim-Erbasli, 2022) and Runge et al (Runge et al, 2022).…”
Section: Related Workmentioning
confidence: 99%